Young EFL learners' processing of multimodal input: Examining learners' eye movements. (February 2019) - Tragant Mestres, Elsa; Pellicer-Sánchez, Ana
Abstract: The use of materials combining verbal and nonverbal input in the EFL/ESL classroom is supported by theories of information processing and is a feature of most instructional practices designed for children. Previous research has shown that the combination of input modes leads to improved learning experiences. However, little is known about how learners direct their attention to the different sources of input in multimodal materials. The present study followed a within-subjects design in which two groups of young EFL learners (n = 19, n = 17) were exposed to two types of multimodal materials: an illustrated storybook with audio support, and a video with foreign language subtitles. Exploration of learners processing of picture and textual areas was carried out with eye-tracking and results indicate that learners spent more time processing the text than processing the visual input in both formats. In the case of the book format, regular and uniform patterns of reading behavior were found whereas in the case of the video condition a high degree of variability was observed. In sum, this study confirms that storybooks and subtitled videos are appropriate materials to engage students with reading since the visual information does not distract their attention from the text.